PENGARUH MODEL PEMBELAJARAN TWO STAY TWO STRAY BERBANTUAN MEDIA INTERAKTIF TERHADAP HASIL BELAJAR BMR SISWA KELAS VA SDN 192 PEKANBARU - Astika Yuliani; Guslinda; Munjiatun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research was motivated by the lack of research on local content subjects, namely Riau Malay Culture. In fact, it tends to be only compulsory subjects that are the focus for improving learning. Observation results show that there are difficulties for students in learning Malay Arabic reading and writing materials, due to students' lack of ability to understand hijaiyah letters and Malay Arabic letters. The use of monotonous learning models applied by teachers also makes students not develop and are not active in the learning process. One alternative learning model that can be used in learning Riau Malay Culture is using the two stay two stray learning model with the help of interactive media in the form of the Canva application. The results of calculating the coefficient of the simple linear regression test equation show that tcount is 5.989 > ttable 2.048 with a significance value of 0.000 < 0.05, so H0 is rejected and Ha is accepted. This means that variable X influences variable Y. Meanwhile, the determination calculation is 58.0%. This shows that the two stay two stray learning model assisted by interactive media influences the BMR learning outcomes of class VA students at SDN 192 Pekanbaru and provides a contribution of 58.0% with the remainder influenced by other factors.